2014
DOI: 10.2967/jnumed.114.141887
|View full text |Cite|
|
Sign up to set email alerts
|

Gleason Score at Diagnosis Predicts the Rate of Detection of 18F-Choline PET/CT Performed When Biochemical Evidence Indicates Recurrence of Prostate Cancer: Experience with 1,000 Patients

Abstract: A high GS at diagnosis is a strong predictive factor for positive (18)F-choline PET/CT scan results for recurrent PCa, even when the PSA level is low (i.e., ≤1 ng/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 31 publications
3
53
1
1
Order By: Relevance
“…In a larger study, Cimitan et al demonstrated that a Gleason score ≥7 was an independent predictive factor for positive PET/CT, even with a low trigger PSA. 30 We did not find ADT administration at the time of the scan to negatively affect the detection rate, which is consistent with Chondrogiannis et al 31 In our study, PET/CT did not add significant value to the MRI diagnosis in context of local recurrence. In fact, pelvic MRI remains the modality of choice, with a sensitivity as high as 91% in the context of biochemical recurrence after RP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a larger study, Cimitan et al demonstrated that a Gleason score ≥7 was an independent predictive factor for positive PET/CT, even with a low trigger PSA. 30 We did not find ADT administration at the time of the scan to negatively affect the detection rate, which is consistent with Chondrogiannis et al 31 In our study, PET/CT did not add significant value to the MRI diagnosis in context of local recurrence. In fact, pelvic MRI remains the modality of choice, with a sensitivity as high as 91% in the context of biochemical recurrence after RP.…”
Section: Discussionsupporting
confidence: 91%
“…27,[29][30][31] We found the best threshold values to predict PET/CT positivity to be a trigger PSA of 2.6 ng/mL, PSAV of 2.0 ng/mL/year, and PSADT of 4.4 months. In comparison, Rodado-Marina et al reported a trigger PSA of 3.5 ng/mL (sensitivity 64%, specificity 76%) and PSADT of six months (sensitivity 58%, specificity 58%) while Cimitan et al reported a sensitivity of 79.5% and specificity of 67% for a trigger PSA of 2 ng/mL.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is of equal importance to identify those individuals within low-yield groups who do have additional risk factors that increase the likelihood of positive, managementchanging imaging procedures. This is underlined by the study of Cimitan et al suggesting that high initial Gleason scores identify patients with PSA levels of between 1 and 2 ng/mL in whom a positive 18 F-choline PET/CT result is more likely (6). In order to progress to evidence-based inclusion in guidelines, these data support the step from descriptive patient studies toward prospective clinical studies with a significant impact on individualized patient management in clinical practice, addressing the impact on patient management, treatment selection, patient outcome, quality of life, and cost-effectiveness of 18 Fcholine PET/CT.…”
Section: Resultsmentioning
confidence: 97%
“…In this issue of The Journal of Nuclear Medicine, Cimitan et al report the results of 18 F-choline PET/CT in a cohort of 1,000 prostate cancer patients with biochemical recurrence after potentially curative surgery or radiotherapy (6). Despite being retrospective and observational, with the inherent methodologic limitations, this study made several clinically relevant observations on this large patient group.…”
Section: See Page 209 Choline Pet/ctmentioning
confidence: 94%